(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2022)
The present study traces a carbonate lamination in microbial mats in a siliciclastic coastal environment. The aim of this paper is to determine how physicochemical and biological processes influence the preservation of sedimentary structures such as ripple marks, covering it by carbonate precipitation. Such precipitation is a combination of the activity of microorganisms, and physicochemical factors. Biological factors, such as photosynthesis, composition and activity of the microbial community, and presence of exopolymeric substances (EPS), play a significant role in coastal environments, while high-energy hydrodynamic events supply seawater, providing calcium and carbonate ions, and trigger events like sediment transport, deposition, and erosion. The combination of these hydrodynamic events with the microbial activity creates physical sedimentary structures, such as ripple marks, which can be biostabilized. The study was conducted in Paso Seco (40°38’40´´S; 62°12´22´´W), a modern coastal flat within an elongated semi-closed basin colonized by microbial mats and categorized as a supratidal zone. Water samples were taken from different ponds within the flat with different degrees of evaporation, and in a tidal creek for hydrochemical analyses. Seawater level fluctuations were measured in the tidal flat over a 10-month period in 2018 using a HOBO water level logger. Ripple field formation over the tidal flat was documented after the occurrence of a strong storm and was monitored throughout three subsequent field trips, and sedimentary samples were taken in a field trip. Petrographic studies show a laterally continuous dense micritic calcite layer, 100–200 µm in thickness, covering the ripple structure, improving the preservation of these bedforms. The presence of microorganisms in the sedimentary environment enables the stabilization of ripple marks because their motility and abundant EPS secretion bind the sediment grains and generate an organic layer that protects them from erosion. On the other hand, the presence of microbial mats contributes to the early preservation of the ripples because they create the adequate conditions for carbonate precipitation. Our observations of modern sedimentary structures and the in situ study of their evolution and early lithification may provide an indicator of microbial colonization and stabilization of ripples in the paleoenvironmental reconstruction.